Comparative evaluation of the effectiveness of dental implants in patients with atrophy of the jaw bones with short implants and longer implants - Акопян , Гагик; Бояджян, А.; Джилажян, А.; Гамбарян, Н.; Сейранян, В.; Геворгян, С.; Хачатрян, А. (Actual Dentistry, 2021)
The aim of this study is to compare the survival rate of dental implants with short implants (< 8 mm) and longer implants ( 8 mm) in patients with atrophy of the jaw bones. Materials and research methods. This study is based on the analysis of treatment outcomes in 107 patients, 59 of whom received short implants (< 8 mm) and 48 patients received implants ( 8 mm) using a combination of augmentation. The study determined the engraftment of 5–6 mm Bicon implants and compared it with that of other implant sizes: Results. The average loss of marginal bone after one year was 0.96±0.25 mm for short implants and 0.94±0.46 for long implants. The survival rate of short implants (6–8 mm) after 3 years was 97.8 %, the survival rate of long (10–13 mm) implants was 98.1 %. The patients were satisfied with the aesthetic and functional result of the treatment. The results showed that implantation using short ones is effective in improving the chewing ability of patients in patients with atrophy of the jaw bones. In difficult clinical conditions, with a pronounced bone tissue deficiency, the use of short implants is the most gentle surgical method for restoring the missing support of fixed prostheses. Key words: atrophy of the jaw bones, dental implantation, short implants.